2017
DOI: 10.1093/rb/rbx014
|View full text |Cite
|
Sign up to set email alerts
|

A novel akermanite/poly (lactic-co-glycolic acid) porous composite scaffold fabricated via a solvent casting-particulate leaching method improved by solvent self-proliferating process

Abstract: Desirable scaffolds for tissue engineering should be biodegradable carriers to supply suitable microenvironments mimicked the extracellular matrices for desired cellular interactions and to provide supports for the formation of new tissues. In this work, a kind of slightly soluble bioactive ceramic akermanite (AKT) powders were aboratively selected and introduced in the PLGA matrix, a novel l-lactide modified AKT/poly (lactic-co-glycolic acid) (m-AKT/PLGA) composite scaffold was fabricated via a solvent castin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…The solvent casting and particulate leaching (SCPL) method, which combines the particulate leaching method and solvent casting method, has been used to produce scaffolds for the culture of osteoblasts and osteogenic differentiation of stem cells [ 110 ]. Mouse embryonic osteoblast cells (MC3T3-E1) cultured on PLGA scaffolds made with the SCPL method showed increased alkaline phosphatase activity and expression of type I collagen [ 111 ]. Emulsion templating is one of the common methods for the fabrication of porous scaffolds [ 16 ].…”
Section: Applications Of Biomaterials In 3d Cell Culturementioning
confidence: 99%
“…The solvent casting and particulate leaching (SCPL) method, which combines the particulate leaching method and solvent casting method, has been used to produce scaffolds for the culture of osteoblasts and osteogenic differentiation of stem cells [ 110 ]. Mouse embryonic osteoblast cells (MC3T3-E1) cultured on PLGA scaffolds made with the SCPL method showed increased alkaline phosphatase activity and expression of type I collagen [ 111 ]. Emulsion templating is one of the common methods for the fabrication of porous scaffolds [ 16 ].…”
Section: Applications Of Biomaterials In 3d Cell Culturementioning
confidence: 99%
“…These results showed that nanochitosan/PPy–Alg scaffold promoted OLN-93 neural cells adhesion and the cells expressed their characteristic morphology. Previous studies have shown that the surface characteristics of scaffolds significantly affect cell adhesion and hydrophilic surface of scaffolds were favorable for attachment of the cells to scaffolds 35 . Moreover, chitosan nanoparticles in scaffolds probably have a role in nanoparticles-dependent attachment via involving in the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Solvent casting and particulate leaching method was a commonly used method for fabrication of porous polymer scaffold, which is owing to the simple operation, and the pore size and the porosity of scaffolds could be well controlled via the particle size and the amount of the incorporated salt particles [14]. Many literatures have demonstrated that the pore size larger than 300 μ m is considered as a suitable dimension for osteocyte ingrowth [1517].…”
Section: Introductionmentioning
confidence: 99%